ArtClimateRoad and Revelations: Wood textures and experiential metaphors. Issue 4 (December 2021) - Thorsnes, Tollef
This Multimodal Sensations article explores embodied experiential metaphors. It focuses on the salient modalities of interaction with wood texture. As both an artist and researcher, I have been particularly concerned with how social semiotic theory can be applied to my work, and specifically, how concepts from multimodal analysis can be transformed into the process of multimodal artistic creation. This article reflects on an example linking a historic anniversary, the texture of ancient wood and interaction of a local participant audience. The analysis applies a combination of concepts gleaned from the theories of Theo van Leeuwen (2016), Juhani Pallasma (2012) and Kjetil Røed (2019) to participant reflections from an art project called ArtClimateRoad.